The Urban-Rural Gap in Health Care Infrastructure – Does Government Ideology Matter? - Niklas Potrafke; Felix Rösel (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2019)
Spatial inequalities in publicly provided goods such as health care facilities have substantial socioeconomic effects. Little is known, however, as to why publicly provided goods diverge among urban and rural regions. We exploit narrow parliamentary majorities in German states between 1950 and 2014 in an RD framework to show that government ideology influences the urban-rural gap in public infrastructure. Leftwing governments relocate hospital beds from rural regions. We propose that leftwing governments do so to gratify their more urban constituencies. In turn, spatial inequalities in hospital infrastructure increase, which seems to influence general and infant mortality.
Keywords: D72; H42; I18; 330; Publicly provided goods; spatial inequalities; political business cycles; partisan politics; government ideology; health care; hospitals